Plasmodium chabaudi‐infected mice spleen response to synthesized silver nanoparticles from Indigofera oblongifolia extract. (11th September 2020) - Al‐Quraishy, S.; Murshed, M.; Delic, D.; Al‐Shaebi, E.M.; Qasem, M.A.A.; Mares, M.M.; Dkhil, M.A.
Abstract: Malaria is a worldwide serious‐threatening infectious disease caused by Plasmodium and the parasite resistance to antimalarial drugs has confirmed a significant obstacle to novel therapeutic antimalarial drugs. In this article, we assessed the antioxidant and anti‐inflammatory activity of nanoparticles prepared from Indigofera oblongifolia extract (AgNPs) against the infection with Plasmodium chabaudi caused in mice spleen. AgNPs could significantly suppress the parasitaemia caused by the parasite to approximately 98% on day 7 postinfection with P. chabaudi and could improve the histopathological induced spleen damage. Also, AgNPs were able to increase the capsule thickness of the infected mice spleen. In addition, the AgNPs functioned as an antioxidant agent that affects the change in glutathione, nitric oxide and catalase levels in the spleen. Moreover spleen IL1β, IL‐6 and TNF‐α‐mRNA expression was regulated by AgNPs administration to the infected mice. These results indicated the anti‐oxidant and the anti‐inflammatory protective role of AgNPs against P. chabaudi ‐induced spleen injury. Abstract : Significance and Impact of the Study: Due to the resistance of the Plasmodium parasite to antimalarial drugs, only a few attempts have been made to use nanocarriers with the specific targeting approach in malaria treatment. In this article, we verified the antioxidant and anti‐inflammatory activity of silver nanoparticles prepared from Indigofera oblongifolia extract (AgNPs) against the Plasmodium chabaudi ‐induced infection in mice spleen. Consequently, the findings obtained detect that AgNPs may be investigated as candidates of promise for therapeutic applications. In addition, our study offers important insights into the spleen response to infection as well as the promising use of AgNPs to combat P. chabaudi ‐induced malaria.